Nonlinear Seismic Behavior of Different Boundary Conditions of Transmission Line Systems under Earthquake Loading - Li Tian; Xia Gai (Shock and Vibration, 2016)
Nonlinear seismic behaviors of different boundary conditions of transmission line system under earthquake loading are investigated in this paper. The transmission lines are modeled by cable element accounting for the nonlinearity of the cable. For the suspension type, three towers and two span lines with spring model (Model 1) and three towers and four span lines’ model (Model 2) are established, respectively. For the tension type, three towers and two span lines’ model (Model 3) and three towers and four span lines’ model (Model 4) are created, respectively. The frequencies of the transmission towers and transmission lines of the suspension type and tension type are calculated, respectively. The responses of the suspension type and tension type are investigated using nonlinear time history analysis method, respectively. The results show that the responses of the transmission tower and transmission line of the two models of the suspension type are slightly different. However, the responses of transmission tower and transmission line of the two models of the tension type are significantly different. Therefore, in order to obtain accurate results, a reasonable model should be considered. The results could provide a reference for the seismic analysis of the transmission tower-line system.